Constructing Sovereignty in Crisis: A Constructivist Analysis of Liberia’s Ebola Response - Michlyne Nyenegahn Williams (European Scientific Journal, ESJ, 2025)
This article examines how Liberia established its sovereignty, legitimacy, and international identity during the Ebola crisis of 2014-2015. While many existing research focus on institutional weaknesses and material dependence, this study employs a constructivist perspective to highlight how ideational and normative factors influenced Liberia’s response.By conducting a discourse analysis of governmental communications, UN resolutions, international reports, and media coverage, the study explores how Liberia framed its crisis management, engaged with international partners, and presented itself as a legitimate state under global scrutiny. The findings indicate that Liberia’s response was shaped not only by resource constrains but also by a conscious process of aligning with international norms, constructing its identity, and asserting its legitimacy. By analyzing Liberia’s experience, this article contributes to discussions on global health governance, African statehood, and the relevance of Constructivist theory in international relations.